Sistem Pendukung Keputusan Pemberian Bantuan Kepada Keluarga Kurang Mampu Menggunakan Metode AHP - Bobby Gersonta Ginting; Fricles A Sianturi (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2021)
Poverty is a problem that is still faced by several countries in the world, especially in Indonesia. Poverty is a condition / condition of the inability of individuals / groups of people to meet the necessities of life, both physical and economic conditions. The system of providing assistance carried out by the Social Service of North Sumatra Province uses the Analytical Hierarchy Process method. The method used in this aid system is the Analytical Hierarchy Process method in the Social Service of North Sumatra Province. The results of the weighted assumptions for each criterion are relative in nature. The criteria used in determining the receipt of assistance are job criteria, income criteria, nutritional consumption criteria (chicken, meat, milk), criteria for sources of information, criteria for medical ability, criteria for the last education of the head of the family. The method used in this research is the AHP method. AHP method is one of the methods used in the Decision Support System to determine the provision of this assistance is the Analytical Hierarchy Process (AHP). After getting the consistency index value, then look for the consistency ratio value (CR) by dividing the consistency index by the consistency random index (RI), namely CR = C1 / R1 CR = 0.09975 / 1.24 = 0.0891, the requirement for consistency CR 0.1 then the CR value that is obtained from the comparison above it is consistent.